Secrets and Silence: Agency of Young Women Managing HIV Disclosure. Issue 8 (16th November 2020) - Mackworth-Young, Constance R. S; Bond, Virginia; Wringe, Alison
ABSTRACT: Drawing on a 12-month ethnography with young women living with HIV in Zambia, we explore their everyday strategies to avoid unintentional disclosure of their HIV status. Young women practiced secrecy with sexual partners, through hiding their antiretroviral therapy and using veiled language around HIV. Whilst remaining silent about their HIV status enabled them to maintain identities beyond HIV, this secrecy triggered feelings of guilt and anxiety, suggesting that their agency was "bounded" by the context of persistent stigma. These strategies to hide their HIV status question public health narratives urging disclosure, and support disclosure-counseling approaches that champions choice.